Identifying Candidate Genes for Short Gestation Length Trait in Chinese Qingping Pigs by Whole-Genome Resequencing and RNA Sequencing - Liu, Zezhang; Yang, Jun; Li, Hong; Zhong, Zhuxia; Huang, Jian; Fu, Jie; Zhao, Hucheng; Liu, Xiaolei; Jiang, Siwen (Frontiers in Genetics, 2022)
Gestation length is a complex polygenic trait that affects pig fetal development. The Qingping (QP) pig, a Chinese native black pig breed, is characterized by short gestation length. However, the genetic architecture of short gestation length is still not clear. The present study aimed to explore the genetic architecture of short gestation length in QP pigs. In this study, selective sweep analyses were performed to detect selective sweep signatures for short gestation length trait between 100 QP pigs and 219 pigs from 15 other breeds. In addition, differentially expressed genes for short gestation length between QP pigs and Large White pigs were detected using RNA sequencing. Comparing candidate genes from these methods with known genes for preterm birth in the database, we obtained 111 candidate genes that were known preterm birth genes. Prioritizing other candidate genes, 839 novel prioritized candidate genes were found to have significant functional similarity to preterm birth genes. In particular, we highlight EGFR, which was the most prioritized novel candidate relative to preterm birth genes. Experimental validations in placental and porcine trophectoderm cells suggest that EGFR is highly expressed in the QP pigs with short gestation length and could regulate the NF-κΒ pathway and downstream expression of PTGS2. These findings comprehensively identify candidate genes for short gestational traits at the genomic and transcriptomic levels. These candidate genes provide an important new resource for further investigation and genetic improvement of gestation length.